Blink reflex and prepulse inhibition in fibromyalgia. Issue 3 (March 2016) - Kofler, M.
Abstract : Patients with fibromyalgia syndrome (FMS) show increased sensory processing of nociceptive and non-nociceptive stimuli. They perceive somatosensory stimuli differently and show altered cortical sensory representation maps following peripheral stimulation. Altered sensory gating may play a causal role. Blink reflex, blink reflex excitability recovery, and prepulse inhibition of the blink reflex – representing brainstem excitability – were assessed in 10 female patients with FMS and 26 female healthy controls. Unconditioned blink reflex characteristics (R1 latency and amplitude, R2 and R2c latency and area-under-the-curve) did not differ significantly between patients and controls. However, blink reflex excitability recovery was enhanced in patients versus controls at all intervals tested. Prepulses significantly suppressed R2 area and increased R2 latency in patients and controls, but patients showed significantly less R2 area suppression than controls (patients: to 80.0 ± 28.9%, controls: to 47.8 ± 21.7%). The general pattern of corresponding changes in R2c was similar. Blink reflex is normal, whereas blink reflex excitability recovery is enhanced, and blink reflex prepulse inhibition is reduced, in patients with FMS, suggesting functional changes at the brainstem level in FMS. Reduced blink reflex prepulse inhibition concurs with altered sensory gating in patients with FMS.